Enantioselective construction of six- and seven-membered triorgano-substituted silicon-stereogenic heterocycles - Chen, Shuyou; Mu, Delong; Mai, Pei-Lin; Ke, Jie; Li, Yingzi; He, Chuan (Nature communications, 2021)
The exploitation of chirality at silicon in asymmetric catalysis is one of the most intriguing and challenging tasks in synthetic chemistry. In particular, construction of enantioenriched mediem-sized silicon-stereogenic heterocycles is highly attractive, given the increasing demand for the synthesis of novel functional-materials-oriented silicon-bridged compounds. Here, we report a rhodium-catalyzed enantioselective construction of six- and seven-membered triorgano-substituted silicon-stereogenic heterocycles. This process undergoes a direct dehydrogenative C−H silylation, giving access to a wide range of triorgano-substituted silicon-stereogenic heterocycles in good to excellent yields and enantioselectivities, that significantly enlarge the chemical space of the silicon-centered chiral molecules. Further elaboration of the chiral monohydrosilane product delivers various corresponding tetraorgano-substituted silicon-stereogenic heterocycles without the loss of enantiopurity. These silicon-bridged heterocycles exhibit bright blue fluorescence, which would have potential application prospects in organic optoelectronic materials. Enantioenriched medium-sized silicon-stereogenic heterocycles are in high demand due to the potential use in functional materials. Here, the authors show a rhodium-catalyzed enantioselective synthesis of six- and seven-membered tri-organosubstituted silicon-stereogenic heterocycles.